USM BOOSTED WITH RM50,000 WORTH OF LABORATORY PRODUCTS FROM IKA WORKS (ASIA) - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, March 2015 Universiti Sains Malaysia (USM) recently received sponsorship of laboratory equipment and products worth RM50,000 from IKA Works (Asia) Sdn Bhd at its Main Campus here. In the sponsorship collaboration signing ceremony, USM was represented by its ViceChancellor, Professor Dato’ Dr. Omar Osman, while IKA Works (Asia) by its Managing Director (Lab/Analytical Technology), Tobias Aman.